The methodology of modelling taxi rank service - Butkevičius, Jonas; Juozapavičius, Algimantas (Transport, 2003)
The operation of a taxi rank as a passengers' transportation service was not researched till now by means of scientific methods. Authors of this article are suggesting the methodology for the analysis and evaluation of a taxi rank as a passengers' transportation system, when passengers pick up a taxi at taxi ranks. According to the analysis of the collected data the assumption has been made that the number of passengers coming to a taxi rank, as well as the number of taxis arriving to take passengers at a rank are distributed by Poisson distribution law controlled by specific values of parameters. This observation enables us to consider a taxi rank as a queueing system, having behavior controlled by two parameters: the expected number of taxis arriving to the rank at a time period and the expected number of passengers picking up a taxi at a rank at the same period of time. Usually values of these parameters do not coincide what makes the modelling of a taxi rank a valuable queueing system. Theoretical considerations as well as practical formulas of this at1icle lead us to the methodology of modelling the demand for taxis at a taxi rank. The methodology suggested enables to estimate the efficiency of taxi rank functioning from different points of view. A taxi company may evaluate the costs related to the outage time of a taxi, as well as the amount of taxis in a rank satisfying the demand of passengers for transportation.First Published Online: 19 Dec 2011